Self‐harm in nurses: prevalence and correlates. (28th April 2016) - Cheung, Teris; Yip, Paul S.F.
Abstract: Aims: The aim of this study was to examine the weighed prevalence of self‐harm and its correlates among Hong Kong nurses. Background: Recent epidemiological data suggest that the weighted prevalence of past‐year suicidality among Hong Kong nurses was found to be 14·9%. Deliberate self‐harm was a significant correlate of suicidality. Nonetheless, there are few population‐based studies exploring the prevalence of self‐harm and its correlates among medical occupational groups in Asia. Design: The study uses a cross‐sectional survey design. Method: Data were collected in Hong Kong over a four‐week period from October–November 2013. Statistical methods, including binary and multivariate logistic regression models, were used to examine the weighted prevalence of self‐harm and its associated factors in nurses. Results: A total of 850 nurses participated in the study. Seventy‐nine participants (9·3%) reported self‐harm in the past year. Nurses aged between 25‐44 were at especially high risk of self‐harm. Female nurses reported self‐harm more than male nurses. The most common forms of self‐harm were self‐cutting, striking oneself and poisoning oneself. Clinical experience, chronic illness, relationship crises with family members, a family history of self‐harm, smoking, symptoms of stress and psychiatric disorder were significantly associated with nurses' self‐harm. The positive correlation between psychiatric disorder and self‐harm was confirmed. Conclusions: There is a need for a raft of self‐harm prevention strategies, including a continuous monitoring system in the healthcare setting detecting and managing the risks of self‐harm in nurses as part of the ordinary provision for their well‐being.